ANALISIS PENGARUH PERATAAN LABA TERHADAP KINERJA DAN RISIKO SAHAM PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA (BEJ) (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2003)
This research was designed to examine whether it has any income smoothing influences to the public company stock return and risk in Jakarta Stock Exchange. In addition, this research will examine that the type of industry would influence between of income smoothing with stock return and risk Income smoothing is management effort to manipulate the income by decreasing the income fluctuation. The sample was chosen based on sampling purposive method and achieved as 213 companies. These sample were classified into two types of companies which are doing the income smoothing and which are not by using Eckel Index. Eckel Index compares variation coefficient of selling and income. The income which are use the earnings before tax. Hypothesis examination which are using double linear regression by inserting the variable of company size as control variable. The result shows that those three models assumption do not has any problems. This research result found empirical evidence that there is no an influence of income smoothing to stock return but there is an influence of income smoothing to stock risk In addition, it was found that there is no any influence of the type company to the relationship between income smoothing with stock return and risk